Epithermal Gold and Base Metal Mineralization at Gandy Deposit, North of Central Iran and the Role of Rhyolitic Intrusions (Journal of Sciences, Islamic Republic of Iran)
The Gandy gold-base metal deposit is located in Tertiary Torud-Chahshirin volcano-plutonic range, north of Central Iran. Various styles of gold mineralization occur throughout the range. Mineralization at Gandy occurs in close spatial relation with rhyolitic domes in a caldera setting in a series of narrow brecciated veins. Two mineralogically and spatially different argillic alterations have affected the volcano-sedimentary host unit. The first is a pervasive advanced argillic alteration (kaolinite + quartz) and the other is a vein-controlled quartz with illite assemblage. Ore minerals comprise gold, silver, base metal sulfides and sulfosalt minerals are accompanied by carbonates, quartz and barite. Fluid inclusions in coarse-grained sphalerite have homogenization temperatures ranging from 139 to 345 °C and salinities from 7.9 to 16 wt% NaCl equiv. Data suggest that the main ore deposition mechanism is the mixing of a 300 °C magmatic fluid. Mineralization at Gandy is the product of ascending gas and saline fluid exsolved from crystallizing magma, possibly due to transition from plastic into brittle regime resulting from emplacement of the rhyolitic intrusion, consequent condensation in ground water and mixing. Characteristics of the Gandy deposit are similar to those of gold and base metal-rich epithermal deposits of intermediate-sulfidation state.